2020
DOI: 10.1177/0021998320904146
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of ply splice fiber reinforced composite laminates

Abstract: To fabricate large-scale or unusually shaped composite structures, pieces of reinforcement plies can be spliced to match specific size and shape requirements, forming ply splice structures. The junction of different plies can be considered a defect in the final material, affecting the mechanical properties. In this paper, ply splice carbon fiber reinforced plastics were studied to analyze the fracture mechanism caused by the ply splice, including the effects of the junction geometry and the ply angle. Tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As the loading time increases, the resin damage accumulates and generates cracks that cause fiber breakage resulting in specimen fracture. 13,21 The release of energy at the moment of fracture of the specimen causes the rapid expansion of cracks resulting in delamination failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the loading time increases, the resin damage accumulates and generates cracks that cause fiber breakage resulting in specimen fracture. 13,21 The release of energy at the moment of fracture of the specimen causes the rapid expansion of cracks resulting in delamination failure.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the strength was mainly determined by continuous layers. Chen 13 studied the effect of different splicing angles and component geometry on unidirectional laminate composites. The study revealed that the fracture would occur at the splicing part and develop at the interface between the splicing and the continuous layer.…”
Section: Introductionmentioning
confidence: 99%